Digital PCR detection of microsporidia in household pipe water of patients with microsporidial keratitis - Wararee Sriyuttagrai; Auemphon Mordmaung; Tachpon Techarang; Jakkrit Juhong; Dominik H. Kowanz; Lunla Udomwech (Scientific Reports)
Abstract This is a prospective non-comparative experimental study aimed to investigate the presence of microsporidia in household pipe water of microsporidial keratitis (MK) patients and to describe the patients’ characteristics and behavioral risk factors. This study was conducted at Walailak University Hospital, Thailand, from July 2022 to February 2024. Patients diagnosed with MK were surveyed using a questionnaire to assess personal behaviors and source of household water. Water from faucets of MK patients’ houses were collected for laboratory analysis with digital polymerase chain reaction (dPCR) to detect microsporidia in water samples. The study involved 54 MK patients, with 23 households contributing water samples. Utilizing dPCR analysis, we found that all water samples were contaminated with microsporidia. Level of contamination differed depending on the water source, with households that use untreated water in their plumbing system having significantly higher copies of pathogenic microsporidial DNA. Contrary to traditionally perceived risk from soil contact into eyes, our study identifies household water as an unforeseen potential source of MK. This emphasizes the critical importance of water quality management in preventing the infection.